SERUM RETINOL BINDING PROTEIN (RBP) IBU MENYUSUI DAN BAYINYA DI DUA KABUPATEN DI JAWA BARAT - Sandjaja, Sandjaja; Sudikno, Sudikno (GIZI INDONESIA, 2015)
ABSTRACT Serum retinol concentration is commonly used to determine vitamin A status. Studies show that serum retinol binding protein (RBP) is a surrogate measure of vitamin A. Infant is among groups of high risk in vitamin A deficiency (VAD). Studies show that vitamin A status in lactating mother are associated with that in infant. However, there is no study of association between serum RBP in mother and infant. The objective of this paper is to determine the association of serum RBP in mother and that in infant. The study was conducted at 2 districts in West Java province of 293 pairs lactating mother and breastfed infant aged 6-11 month old of poor families. Serum vitamin A and RBP were measured by HPLC and ELISA respectively. Linear regression was employed to determine association between serum RBP of infant and mother after controlling for other risk factors. Mother’s serum retinol (X+SE) was higher compared to infant (39.0+1.1 and 29.9+0.7 mg/dL). Mother’s serum RBP was also higher in mother than in infant (1.25+0.02 and 0.95 + 0.01 µmol/L). There was a significant association between serum retinol and RBP of mother (r=0.565, p=0.000) and also in infant (r=0.309, p=0.000). There is a significant association between RBP status of mother and infant (r=0.379, p=0.000) controlled by household, mother, and child characteristics. Two main significant factors associated with serum RBP level in infant are serum RBP level of mother (p = 0.000) and infant received high-dose vitamin A capsule (p=0.010). The conclusion is that serum RBP can be used as a surrogate measure of vitamin A status and significant association between serum RBP in lactating mother and her infant. Keywords: retinol binding protein, serum retinol, lactating mother, infant  ABSTRAK Serum retinol umum digunakan untuk menentukan status kurang vitamin A (KVA). Salah satu alternatif menilai KVA adalah serum retinol binding protein (RBP). Beberapa penelitian membuktikan korelasi antara serum retinol ibu menyusui dan bayinya, tetapi belum ada yang meneliti korelasi RBP ibu dan bayinya. Penelitian ini bertujuan untuk mengetahui korelasi serum RBP ibu menyusui dan RBP bayi. Penelitian dilakukan di dua kabupaten di Jawa Barat dengan sampel 293 pasangan ibu menyusui dan bayinya. Serum retinol ditentukan dengan metoda HPLC sedangkan RBP dengan ELISA. Analisis regresi linier digunakan untuk menilai korelasi RBP ibu dan bayi dikontrol dengan faktor risiko lain. Kadar serum retinol (X+SE) ibu menyusui lebih tinggi dibanding bayi (39,0+1,1 and 29,9+0,7 mg/dL). RBP ibu menyusui juga lebih tinggi dibanding RBP bayi (1,25+0,02 and 0,95 + 0,01 µmol/L). Ada korelasi signifikan antara serum retinol dengan RBP baik pada ibu menyusui (r=0,565; p=0,000) maupun pada bayi (r=0,309; p=0,000). Korelasi signifikan dibuktikan antara kadar RBP ibu menyusui dan RBP bayi (r=0,379; p=0,000) dikontrol karakteristik rumahtangga, ibu, dan bayi. Faktor utama yang signifikan menentukan kadar RBP bayi adalah RBP ibu menyusui (p = 0,000) dan bayi menerima kapsul vitamin A 6 bulan terakhir (p=0,010). Serum RBP merupakan alternatif menentukan KVA dan ada korelasi signifikan antara serum RBP ibu menyusui dan bayi.